Exoticism in Gertrude Bell's Persian pictures - Ghaderi, Farah; Wan Yahya, Wan Roselezam (Cambridge University Press, 2014)
Victorian travelers in colonial contexts encountered differences in landscape, mores and manners, society, politics and culture, among other things, and registered their responses to the places visited in their published travel books for the home audience. Postcolonial critics contend that exoticism, i.e., a Western traveler's response to and description of the differences encountered in the context of travel, was deeply informed by the asymmetrical power relation between the representer/colonizer and the represented/colonized. As a result, these critics argue, exoticism in colonial travel writing was appropriative since it tended to construct the dichotomy of self/other in such a way as to justify imperial interventions in other countries (Forsdick, “Sa(L)Vaging Exoticism” 30–34; Said 1–28). As Graham Huggan rightly argues, difference of the colonial other in its various aspects was denigrated and dismissed as exotic when “translated into the master code of empire,” since it superimposed “a dominant way of seeing, speaking and thinking onto marginalised peoples” (24).